HUBUNGAN SELF MANAGEMENT DENGAN KUALITAS HIDUP PASIEN RHEUMATOID ARTHRITIS DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2021 - Anita Gandaria Purba; Kuat Sitepu; Arfah May Sara; Jesiska Yolanda Sirait; Nur Hamida Pohan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Rheumatoid arthritis is a autoimmune that causes a long period of inflammation in the joints. This might cause a deprcrease in the quality of life of a person resulting in limited activity and depression. The purpose of this study was to determine the relationship between self management and the quality of life of patients with rheumatoid arthritis . the research method uses quantitative research by using descriptive correlation research methods. Then this research uses a Cross sectional approach design research method and correlation design with a sampling total sampling, and the number of sample in this study was 25 respondents. The measuring instrument used in this research in a questionnaire. Data analysis was carried out using the chi-square tets, the result of this study showed that 18 people (51%) had a good self management and 17 people (49%) had a good quality of life. This show that there is a relationship between self managemnet and quality of life of rheumatoid arthritis patient at Grandmed Lubuk Pakam hospital in 2021 with the result of the chi-square test (p Value 0,001). Therefore, it is hoped that patients will be able to further improve self management so that the quality of life is getting better.